(untitled) (Fiep Bulletin - online, 2025)
Objective: To analyze the kinematics of front crawl swimming (time, number of strokes, average speed, stroke rate, and stroke length), comparing responses with and without the use of different equipment (fins, paddles, and parachutes) in adolescent swimmers. Methods: Twenty swimmers (13.43 ± 1.86 years old) were randomly subjected to four conditions: a) control (no equipment); b) with fins; c) with paddles; d) with parachutes. Participants were instructed to swim at maximum speed over a 10-meter distance. Results: In males, differences in time and number of strokes were observed when comparing the parachute condition to the others. Stroke length differed between the control and paddles, as well as between parachutes and the other conditions. In females, differences were observed in time between control and fins, fins and paddles; in average speed between control and fins, fins and paddles; in stroke rate between fins and paddles, fins and parachutes; and in stroke length between control and paddles, as well as fins and paddles. Conclusion: The parachute increases crawl swimming time, stroke number, and stroke rate, while reducing average speed and stroke length. Fins tend to increase stroke length, opposite to the number and rate, while fins reduce time and increase average speed.